Sosialisasi Game Edukasi Virtual Quiz Berbasis Mediapipe untuk Sekolah Dasar - Nur Budiman, Saiful; Sri Lestanti; Erwan, Erwan (Kontibusi: Jurnal Kontribusi Kepada Masyarakat, 2024)
Virtual educational game quiz using Mediapipe is one of the innovative and exciting learning methods for 3rd grade elementary schoolchildren at SDN Wonorejo Talun Blitar. This game was created with the aim to help improve children's understanding and knowledge in a variety of subjects in an interactive and fun way. In this game, children will be asked to answer the questions given through video and voice displays using Mediapipe technology. They can answer questions by moving their bodies or showing answers through specific gestures. This will provide a more interactive and educational learning experience for children, so that they can more easily understand the lesson submitted. Besides, virtual educational quiz games can also help improve children's concentration and focus in learning. With a fun and exciting way of playing, children will be more motivated to learn and follow every question well. They will also learn to collaborate and communicate with their friends in search of the right answers. Through these games, children are expected to be able to learn more effectively and efficiently, as well as improve their academic scores at school. They will also become more skilled in using technology and understand lesson concepts better. Thus, a virtual educational quiz game using Mediapipe can be one of the effective and innovative learning methods for 3rd grade elementary schoolchildren at SDN Wonorejo Talun Blitar. For the outdoors proposed by the executive team are publications of scientific journals and virtual games quizzes.